Os "Tesourinhos" de uma Professora Estagiária: de onde venho, onde estou, para onde quero ir - Laura Margarida de Sousa Campos (2024)
The present document, entitled 'The Little Treasures of a Student Teacher: where I come from, where I am, and where I want to go,' is narrated in the first person within the scope of the Professional Practicum included in Teaching Physical Education in the Basic and Secondary School Master's Degree by the Faculty of Sport of the University of Porto. Divided into three main parts - where I come from, where I am, and where I want to go - this Internship Report reflects the experience and growth as a future Physical Education teacher during the supervised teaching practice, carried out over a school year at Ermesinde Secondary School, in a Group composed of four pre-serviceTeachers, supervised by two qualified professionals: a Cooperating Teacher and a Supervising Professor. The document exposes the 'reality shock' faced when teaching a 10th-grade class and a 5th-grade class, addressing personal motivations as well as the challenges encountered on the path to teaching, which proves to be arduous, filled with uncertainties and challenges, yet also rewarding. Furthermore, there is a critical reflection on the construction of professional identity, highlighting the importance of creating an environment of trust and mutual respect with students, as being a teacher goes beyond the transmission of knowledge, playing a key role in the personal and social development of students. Lastly, within the scope of professional development, I address the topic of well-being and job satisfaction among Physical Education teachers, understanding which factors influence teachers in the mentioned parameters.